Extensive pneumoscrotum and pneumoperitoneum simulating a compound inguino scrotal hernia in a neonate - Rebecca Bonny; Ello Nicolas Moh; Yapi Landry Aké; Amenankan Sophie Kouassi; Kokoe Midékor; Jean Paul Kouao; Cheick Coulibaly (Elsevier, 2017)
Pneumoscrotum is defined as being an accumulation of air in the scrotal region. The combination of pneumoperitoneum and pneumoscrotum of bacterial origin is rare and sets diagnostic and therapeutic problems. Objective: To report the case of a neonate who presented a pneumoscrotum combined to a pneumoperitoneum simulating a compound inguino-scrotal hernia. Clinical case: It was a neonate in its 3rd day of life, of a male gender, taken care of, for a left inguino-scrotal swelling which occurred 8 h before its admission. The clinical examination objectivized a voluminous left inguino-scrotal swelling with facing skin ulceration and a basithoracic subcutaneous emphysema. The trans-illumination was positive. An impromptu X-ray photography of the abdomen revealed a gaseous cavity under the diaphragmatical cupola. The biological checkup was disrupted with an anemia at 4 g/dl and a CRP at 48 mg/l. This clinical picture led to the suggestion of a compound constricted left inguino-scrotal hernia. The indication of a surgical exploration by upper inguinal way was set. During the surgery operation, a voluminous air bubble in the left inguino-scrotal region with a moderate scrotal hematoma was found out. A hematoma drainage and a ligation-section of the peritoneum - vaginal canal were carried out. The immediate operative effects were simple with a gradual disappearance of the subcutaneous emphysema. During the surgery operations takings allowed us to isolate Klebsiella pneumonia, and an adapted antibiotic therapy was carried for 10 days. Conclusion: Pneumoscrotum is rare in a neonate. The diagnosis is difficult for it could be confused with other ailments. It is advisable to identify the primary or secondary etiology for an adequate medical care.